New improvements in existing combined-cycles: Exhaust gases treatment with amines and exhaust gas recirculation. (November 2020) - Borge-Diez, David; Gómez-Camazón, David; Rosales-Asensio, Enrique
Abstract: The combined cycle plants in 2019 are upswing due to definitive closure of conventional coal-fired power plants. The price increase of a ton of CO2, will close to 25 euros in 2019, could allow to increase their capacity factor above 50%. It has been already achieved a high flexibility imposed by the regulator of the Spanish network and possible hybridizations, in both gas turbine and heat recovery steam generator. Therefore, one step ahead directed to the reduction and treatment of the flow of exhaust gases at the outlet of the boiler during the operation is necessary. An optimization study based on a parametric analysis of this possible reduction has been carried out, with recirculation of the exhaust gases and the treatment of them with amines in a CO2 capture plant, both at the exit of the boiler, using real data base, to study their possible integration within the existing combined cycle. The results obtained are very promising: firstly, with the use a 35% of exhaust gases recirculation + capture plant in existing combined cycle, the efficiency of the gas turbine improves 0.5%. Secondly, the total number of tons of CO2 avoid per year would be around 633 kilotons (based on a capacity factor in 2019 closed to 0.41). Therefore, the saved cost in ton of CO2 for one existing combined cycle could be around 21.4 million of euros/year. This configuration, therefore, decreases the number of trains from 2 (existing combined cycle + capture plant) to 1.36. This decreasing is traduced in costs reduction and due to it an effective technique for pollutant emissions reduction. On the other hand, the new combined cycle will have an efficiency penalty caused by chemical absorption in the capture plant. The crossover requires approximately 30% of the middle/low steam of the turbine to obtaining 90% capture of CO2 with the corresponding penalty of 4 points in the global cycle performance and a reduction of power close to 21% with respect to the existing cycle. All boil down to a conflict of interests between €/Mw lost vs €/ton CO 2 avoided. Clearly the rising in capacity factor and flexibility in current combined cycle plants will be decisive in future to elucidate this conflict. The results obtained are totally in contrast with other studies carried out being fully feasible for implementation in existing combined cycles.